PERANAN SATUAN RESERSE KRIMINAL DALAM PENYIDIKAN TINDAK PIDANA MUTILASI DI WILAYAH HUKUM KEPOLISIAN DAERAH RIAU (STUDI KASUS MUTILASI DI KABUPATEN SIAK) - Bukti Hasintongan Simanullang; Firdaus '; Erdianto ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Siak is one of the districts in the province of Riau. The Police Siak consisting of 10 policeoffice is in charge of controlling the police agency every crime that occurs in the area. At latelyin the area have the criminal act of mutilation, in which the person in doing so sadistic actionsagainst the victim and the offense is very disturbing Indonesian society in general and inparticular the public Siak. The problem in this paper is what causes of the criminal acts ofmutilation in Riau Police Legal Jurisdiction, and how the role of the Criminal Investigation Unitin the investigation of criminal mutilation, whether the factors that become obstacles in theinvestigation of criminal offenses mutilation in Region Regional Police Law Riau Police Siak,whether the efforts of the Criminal Investigation Unit in addressing the factors that becomeobstacles in the investigation of criminal offenses in the area mutilation Law Riau Police, PoliceSiak, Siak, having done research using empirical methods / sociological, by source data isbacked up by the primary data of primary and secondary data, and after data is collected, the datawere analyzed by means of qualitative and concluding with the deductive method.Based on the research results of the causes of the criminal acts of mutilation in RegionalLaw Riau Police, Police Siak, Siak is due to the instigation of parents to pass on a dark science, astrong desire of the child to gain knowledge of the immune father, because of economic factors ,lack of parental supervision of their child victims, and lambanya performance of the police tofollow up the report, then the role of the Criminal Investigation Unit in the investigation carriedout under the rules of the existing legislation, and the role undertaken belong to the actual role.Then the factors that become obstacles in the investigation of criminal mutilation faced by theCriminal Investigation Unit at the Regional Law Riau Police, Police Siak, Siak is a factor of itsown law, law enforcement apparatus, facilities and infrastructure factors and environmentalfactors or natural, and efforts undertaken to overcome these obstacles is to overcome legalfactors alone no attempt was made, to address the law enforcement apparatus, the first problemof a lack of seriousness, boss investigators provide motivation to each investigator, and tosupervise, the second problem of lack of qualified investigators in the investigation, the CriminalInvestigation Unit in cooperation with the Police Bengkalis, then to overcome infrastructurefactors, the first problem the lack of cars, no attempt was made but still use the car available, thesecond problem of lack of funds, investigators using their own funds and funds specified, the lastto address the environmental or natural factors, investigators continue to work hard to find partsof the body that is not intact and then to overcome the difficulties in identifying the investigatorsends the victim's body parts to Bhayangkara Hospitals Pekanbaru. Suggestions author, it isexpected that all relevant parties running role and functions well.Keywords: Role-Criminal Investigation Unit Crime-Investigation-Mutilation